2023
DOI: 10.7554/elife.85251
|View full text |Cite
|
Sign up to set email alerts
|

Tau polarizes an aging transcriptional signature to excitatory neurons and glia

Abstract: Aging is a major risk factor for Alzheimer’s disease (AD), and cell-type vulnerability underlies its characteristic clinical manifestations. We have performed longitudinal, single-cell RNA-sequencing in Drosophila with pan-neuronal expression of human tau, which forms AD neurofibrillary tangle pathology. Whereas tau- and aging-induced gene expression strongly overlap (93%), they differ in the affected cell types. In contrast to the broad impact of aging, tau-triggered changes are strongly polarized to excitato… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 90 publications
(180 reference statements)
1
1
0
Order By: Relevance
“…S6 ). These findings are consistent with prior single-cell sequencing studies in flies overexpressing mutant human TAU ( Praschberger et al 2023 ; Wu et al 2023 ). We observed regulation of both common and distinct biological pathways when comparing differentially expressed genes across cell subtypes.…”
Section: Discussionsupporting
confidence: 91%
“…S6 ). These findings are consistent with prior single-cell sequencing studies in flies overexpressing mutant human TAU ( Praschberger et al 2023 ; Wu et al 2023 ). We observed regulation of both common and distinct biological pathways when comparing differentially expressed genes across cell subtypes.…”
Section: Discussionsupporting
confidence: 91%
“…Studying cell vulnerability in AD is important to understand disease progression, reveal biomarkers, and identify therapeutic targets. snRNA-seq serves as an ideal method to study cell vulnerability and several recent studies have employed snRNA-seq in different AD models and human patients (Lau et al, 2020; Mathys et al, 2023; Sziraki et al, 2023; Wang et al, 2024; Wu et al, 2023). Out of necessity, most of these studies have focused on a specific brain region and identified specific cell types that are selectively vulnerable.…”
Section: Discussionmentioning
confidence: 99%